2016
DOI: 10.1080/15715124.2016.1159571
|View full text |Cite
|
Sign up to set email alerts
|

Sediment yield in Paraopeba River Basin – MG, Brazil

Abstract: Sediment delivery rate (SDR) is traditionally defined as a fraction of upland gross erosion that is transported through the outlet of a given basin, thus representing an index of the sediment transport efficiency. The objective of this study was to evaluate a model-based approach for SDR determination in the Paraopeba River Basin (PRB), located at the central region of Minas Gerais State, Southeastern Brazil. The empirical model known as RUSLE, which stands for Revised Universal Loss Equation, was used embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The most erodible soils, dominated by Distrofic Latossol (Oxisol), are located in the northern part of the catchment, according to the soil map provided by the Brazilian Agricultural Corporation (EMBRAPA) [67]. The results are also aligned with further literature values in that geographic area, which also assessed that the K Factor for Latossol (Oxisol) is in the range of 0.019-0.026 t ha h ha −1 MJ −1 mm −1 [68][69][70][71]. The western part of the catchment, which is also dominated by Oxisol, showed low soil erodibility with values reaching up to 0.013 t ha h ha −1 MJ −1 mm −1 .…”
Section: K Factorsupporting
confidence: 54%
See 1 more Smart Citation
“…The most erodible soils, dominated by Distrofic Latossol (Oxisol), are located in the northern part of the catchment, according to the soil map provided by the Brazilian Agricultural Corporation (EMBRAPA) [67]. The results are also aligned with further literature values in that geographic area, which also assessed that the K Factor for Latossol (Oxisol) is in the range of 0.019-0.026 t ha h ha −1 MJ −1 mm −1 [68][69][70][71]. The western part of the catchment, which is also dominated by Oxisol, showed low soil erodibility with values reaching up to 0.013 t ha h ha −1 MJ −1 mm −1 .…”
Section: K Factorsupporting
confidence: 54%
“…further literature values in that geographic area, which also assessed that the K Factor for Latossol (Oxisol) is in the range of 0.019-0.026 t ha h ha −1 MJ −1 mm −1 [68][69][70][71]. The western part of the catchment, which is also dominated by Oxisol, showed low soil erodibility with values reaching up to 0.013 t ha h ha −1 MJ −1 mm −1 .…”
Section: K Factormentioning
confidence: 75%
“…This spatial variability has been observed in other studies, like that of De Vente et al (2008), who obtained a SDR that varied from 0.03 to 55% for in 61 subbasins in Spain. Likewise, Van Rompaey, Krasa and Dostal (2007) Water erosion vulnerability and sediment delivery rate in upper Iguaçu river basin -Paraná hand, Beskow et al (2009), examining the Rio Grande River Basin in the state of Minas Gerais, found an average value of 1.62% for a drainage area greater than 6,000 km 2 , whereas Durães, Mello and Beskow (2016), upon inspection of the Paraopeba River Basin's SDR, discovered values varying from 8.6% to 66% for an area of 8,659 km 2 . In accordance with Brown et al (2005), the impacts of alterations in the use of soil in drainage basins concerning superficial runoff can, in general, be evaluated in terms of maximum and minimum outflow.…”
Section: Sediment Delivery Rate (Sdr)mentioning
confidence: 99%
“…As monitoring soil management and conservational practices are difficult to achieve via satellite imaging, since they represent a small portion of the basin, this variable was considered to be 1. It must be highlighted that this same thought was used in various works, such as those of Pradhan et al (2012), Vemu andPinnamaneni (2011), Silva, Montenegro andSantos (2012), Oliveira et al (2014) and Durães, Mello and Beskow (2016). The values of C used in this study were obtained from the literature presented in Table 4.…”
Section: Application Of the Rusle To The Uirbmentioning
confidence: 99%
“…The SDR spatial distribution can be observed in Figure 6B and it is mainly determined by the land topography. However, in some cases, the spatial heterogeneity of the SDR is not represented in the sediment yield modelling in the context of watersheds, and it is computed as a single ratio to multiply by the average gross erosion of the area [7,56]. We found a SDR value of approximately 5% in the Córrego Água Azul catchment.…”
Section: Sediment Delivery Ratio (Sdr)mentioning
confidence: 92%